Spontaneous pneumomediastinum as a potential predictor of mortality in patients with idiopathic pulmonary fibrosis - Colombi, Davide; Tenenbaum, Svenja; Palmowski, Karin; Heußel, Claus Peter; Sverzellati, Nicola; Silva, Mario; Eichinger, Monika; Kreuter, Michael (Respiration, 2016)
Background: Spontaneous pneumomediastinum (PM) is a rare event in patients with idiopathic pulmonary fibrosis (IPF) with unknown prognostic implications. Objectives: To analyze the incidence and prognostic impact of PM in a cohort of patients with IPF. Methods: PM diagnosed by computed tomography was identified retrospectively in the clinical and radiological records of 182 patients with IPF who were admitted to our center between August 2006 and July 2013. PM patients were compared to matched IPF patients not affected by PM and analyzed for survival. Results: PM occurred in 9/182 IPF patients [5%; 6 males; median age: 63 years; median percent predicted of vital capacity (VC%) at baseline: 53%]. The median time between IPF diagnosis and PM occurrence was 3 months (interquartile range: 0-33). The control group included 36 IPF patients (28 males; median age: 69 years; VC% at baseline: 57%). In a multivariate Cox regression analysis, PM was a significant predictor of mortality [hazard ratio (HR): 3.0; p = 0.032]. Considering only patients experiencing PM at the time of IPF diagnosis (n = 4), PM was a strongly significant predictor of mortality in multivariate analysis (HR: 6.4; p = 0.007). Conclusions: Spontaneous PM is a rare but serious complication in patients with IPF and may be considered as a potential predictor of mortality.
Gesehen am 04.06.2020